Using the Discovery Learning Model to Improve Student Learning Outcomes in Indonesian Language Instruction - Fien Pongpalilu (East Asian Journal of Multidisciplinary Research, 2023)
Teachers utilize the learning implementation plan as a guide to help them concentrate the classroom learning process. The primary content is used to build the learning implementation strategy in detail. The content presented in the learning implementation plan is organized into a learning model. In order to inspire students throughout learning, learning models can provide a more engaging and dynamic learning environment. In this study, the researcher examines how the learning implementation plan for the class XII SMK 01 Bengkulu City observation report uses the Discovery Learning learning paradigm. Two of the meetings included in the learning implementation plan were used for research. Triangulation (mixed) procedures are used in qualitative research methodologies to gather data. Reading the Discovery Learning learning model's steps was how the research's data was collected. Using a triangulator, the validity of the findings data was analyzed. The goal of this study is to enable researchers to explain the phases in the learning model for Discovery Learning that are included in the suitable learning implementation plan. 42 pieces of data were found. You will be able to comprehend the observation report's structure at the first meeting, and at the second, you will give an overview of the report's content.